2022
DOI: 10.3390/plants11060791
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Contents in a Mediterranean Population of Plantago lanceolata L. Exploited for Quarry Reclamation Interventions

Abstract: Plantago lanceolata L. (plantain) is an interesting multipurpose perennial species whose aerial parts are used in herbal medicine due to its precious phytochemicals and are palatable to animals. Moreover, peculiar traits such as drought tolerance, an extended growth season and a deep root system, make plantain a promising pioneer plant for quarry reclamation based on the use of native species. This study evaluated the effects of different environmental conditions and seasons on the accumulation of the bioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 49 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…have a role in reduction of inflammation it when used as a moist dressing. And in other studies by (31,32) who explained shortens the inflammatory healing phase associated using of moist dressing and produces good cosmetic results.…”
Section: Discussionmentioning
confidence: 89%
“…have a role in reduction of inflammation it when used as a moist dressing. And in other studies by (31,32) who explained shortens the inflammatory healing phase associated using of moist dressing and produces good cosmetic results.…”
Section: Discussionmentioning
confidence: 89%
“…Plantain ( Plantago lanceolata ) has been used since ancient times in traditional medicine, either as such or in the form of tinctures, decoctions, or infusions. At the base of the medicinal properties are the active principles [ 1 , 2 , 3 , 4 , 5 ], with antioxidant, and antitumor properties [ 6 , 7 , 8 , 9 ] as polysaccharides [ 10 , 11 , 12 ], polyphenols [ 3 , 5 , 8 ] alkaloids, terpenoids (ursolic acid, oleanolic acid), caffeic acid derivatives (plantamajoside, acteoside or verbascoside), iridoid glycosides (aucubin, catalpol), fatty acids (palmitic acid, linolenic acid, linoleic acid, myristic acid), vitamins [ 1 , 2 , 3 ], macroelements and microelements [ 13 ]. Analytical studies performed on the essential oil obtained by hydrodistillation from the leaves of Plantain showed that it contains a wide range of organic compounds, with fatty acids representing about 41% of the oils fraction [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…were loliolid, ursolic acid, oleanolic acid, and sitosterol acid 18 β-glycyrrhetinic. Another important class in Plantaginaceae is that of iridoid glycosides; aucubin was noticed as the main iridoid glycoside in Plantago major —this species may also contain small quantities of asperuloside, majoroside, 10-hydroxymajoroside, 10-acetoxymajoroside, catapol, gardoside, geniposidic acid, melittoside [ 1 , 8 ]. The iridoid glycosides content from Plantago lanceolata attain 2–3% ( w / w ); the main compounds found here are acucubin, catalpol, asperuloside, globularin, and desacetylasperuloside-acid methyl ester [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations